Probiotic Effectiveness in Children Less than Five Years Old with Perennial Allergic Rhinitis: A Randomized Controlled Trial - Abdul Qadir, Ammara Manzoor, Abdul Ghaffar Khan, Ibrahim, Zarmast Khan, Aummara Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to evaluate the effectiveness of probiotics in treating perennial allergic rhinitis in children younger than five and to compare them to cetirizine. Study Design: A randomized controlled trial Place and Duration: This study was conducted at Mohtarma Benazir Bhutto Shaheed Medical College Mirpur & Child specialist New City Teaching Hospital Mirpur AJK in the duration from July, 2022 to December, 2022. Methods: There were 160 children with allergic rhinitis had age 3-60 months were included in this study. After getting informed written consent from the parents of children detailed demographics were recorded. Symptoms of presented cases were recorded. Patients were equally divided in two groups. Group I received cetirizine in 80 cases and in group II 60 cases received probiotics LP-33 for 5-weeks. Post treatment efficacy and adverse events among both groups were compared. SPSS 23.0 was used to analyze all data. Results: Mean age of the cases was 27.6±8.53 months with mean weight 12.6±11.81 kg. among 160 children, 94 (58.8%) cases were males and 66 (41.2%) children were females. Majority 82 (51.3%) cases had nasal blocking, sneezing in 80 (50%) cases, coughing in 75 (46.9%) cases, sleeping difficulties in 72 (45%) and feeding difficulties in 69 (43.1%) cases. After 5 weeks, in group I efficacy found in 72 (90%) cases and in group II 69 (86.3%) cases showed improvement, difference was insignificant (p>0.05P).Post treatment adverse outcomes in group I was 2 (2.5%) and in group II there was no any side effect found. Conclusion: In this study, we found that probiotic (LP-33) was just as effective as cetirizine in treating perennial allergic rhinitis in children less than five years old. The study found that unlike conventional treatments, probiotics had no negative effects on children with allergic rhinitis. Keywords: Allergic Rhinitis, Probiotic, Cetirizine, Perennial, Rhinorrhea